Predictors of long length of hospital stay among elders admitted with seizures in a tertiary centre: a prospective study - BACELLAR, Aroldo; ASSIS, Telma Rocha de; PEDREIRA, Bruno Bacellar; CÔRTES, Luan; SANTANA, Silas; NASCIMENTO, Osvaldo José Moreira do (Arquivos de Neuro-Psiquiatria, 2020)
Population ageing is a global phenomenon, and life expectancy in Brazil is growing fast. Epilepsy is the third most important chronic neurological disorder, and its incidence is higher among elderly patients than in any other segment of the population. The prevalence of epilepsy is greater among inpatients than in the general population and it is related to long length of hospital stay (LOS), which is associated with hospital mortality and higher healthcare costs. Despite these facts, reports of elderly inpatients admitted with seizures and associated outcomes are scarce. Objective: To identify predictors of long LOS among elderly inpatients admitted with seizures. Methods: We prospectively enrolled elders admitted with epileptic seizures or who experienced seizures throughout hospitalization between November 2015 and August 2019. We analysed demographic data, neurological disorders, clinical comorbidities, and seizure features to identify risk factors. Results: The median LOS was 11 days, with an interquartile range (IQR) of 5-21 days. The frequency of long LOS (defined as a period of hospitalization ≥12 days) was 47%. Multivariate analysis showed there was an exponential increase in long LOS if a patient showed any of the following conditions: intensive care unit (ICU) admission (OR=4.562), urinary tract infection (OR=3.402), movement disorder (OR=5.656), early seizure recurrence (OR=2.090), and sepsis (OR=4.014). Conclusion: Long LOS was common among elderly patients admitted with seizures, and most predictors of long LOS found in this cohort might be avoidable; these findings should be confirmed with further research.
Keywords: Epilepsy; Seizure; Aged; Length of Stay; Risk Factors